Algal Active Ingredients and Their Involvement in Managing Diabetic Mellitus - Aijun Tong; Dengwei Wang; Nan Jia; Ying Zheng; Yusong Qiu; Weichao Chen; Hesham R. El-Seed; Chao Zhao (Biology)
Diabetes mellitus (DM) is becoming increasingly prominent, posing a serious threat to human health. Its prevalence is rising every year, and often affects young people. In the past few decades, research on marine algae has been recognized as a major field of drug discovery. Seaweed active substances, including algal polysaccharides, algal polyphenols, algal unsaturated fatty acids, and algal dietary fiber, have unique biological activities. This article reviews the effects and mechanisms of the types, structures, and compositions of seaweed on inhibiting glucose and lipid metabolism disorders, with a focus on the inhibitory effect of active substances on blood glucose reduction. The aim is to provide a basis for the development of seaweed active substance hypoglycemic drugs.